Polyglutamine Diseases after Genetic Analysis in Patients Clinically Diagnosed as Parkinson’s Disease in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Polyglutamine (polyQ) diseases are Huntington's Disease (HD), Dentatorubropallidoluysian Atrophy (DRPLA), Spinobulbar Muscle Atrophy (SBMA) and the Spinocerebellar Ataxias (SCA) type 1, 2, 3, 6, 7 and 17. These diseases are characterized by an expansion of the CAG-trinucleotide repeat region in the respective disease-related genes.Objective: To find out Polyglutamine (polyQ) diseases by genetic analysis from those patients presenting with Parkinsonism in the Neurology department of Mymensingh Medical College hospital.Materials and Methods: This study was conducted on 7 healthy people and 9 patients of Neurology Department, Mymensingh Medical College Hospital in 2010. 5ml blood was collected from each individual by venipuncture. The complaints of patients along with physical and/or psychological findings, family history including demographic data were recorded with a questionnaire by the neurologists of Hospital. Informed consents from the patients were taken and ethical clearance sought as well. Extraction of genomic DNA from the venous blood using FlexiGene DNA kit (Qiagen, Japan) was performed in Faculty of Veterinary Science, Bangladesh Agricultural University, Mymensingh, Bangladesh. The extracted DNA was stored, accumulated and were sent to Division of Clinical Genetics, Department of Medical Genetics, Osaka University Medical School, Suita, Osaka 565 0871, Japan for PCR and further analysis up to amplification.Results: HD PCR products reveal the DNA product of about 110bp (no. of CAG repeats=21) to 150bp (no. of CAG repeats=34) in both healthy individual and patient repeats=36). SCA2 PCR products reveal the DNA products of about 150 bp (no. of CAG repeats=23) except one patient and it was 175bp (no. of CAG repeats=30). SCA3 PCR product size of both healthy individual and patient DNA was within about 250 (no. of CAG=11) to 300 bp (no. of CAG repeats=28) except one patient which was about 320bp and its CAG repeats was about 34. SCA6 PCR product size of both healthy individual and patient DNA was about 150bp (no. of CAG=16). DRPLA PCR product size of healthy individual and patients DNA was about 142 (no. of CAG repeats=19) to 165bp (no. of CAG repeats=27) except one healthy individual DNA which was about 205 bp and its CAG repeat was 40.Conclusion: Genetic analysis and PCR has been an important tool to visualize the root cause of the diseasesthe CAG repeat can facilitate a definitive clue to address Poly Q diseases.This is so far first time study in Bangladesh on the range of CAG repeats in patients as well as healthy individual.Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 44-49